THE MANAGEMENT OF RELIGION-BASED CHARACTER EDUCATION AT THREE MADRASAH IBTIDAIYAH IN GORONTALO PROVINCE - Hasbi, Muhammad; Sonhadji, Ahmad; Huda, Muhammad; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The main objective of this qualitative research was to describe themanagement of relogion-based character education at the Madrasah Ibtidaiyah(MI) in Gorontalo Province, Indonesia. Location of the research were in MITerpadu Al Ishlah, MI Muhammadiyah, and MI Almourky. The researchfindings indicate that (1) planning activities of character education atMadrasah was based on the vision and mission of the institution which was setup by school boards and teachers to deciced program and subject contents ofcharacter education, (2) the implementation of character education wasinitiated by encouraging the teaching of core values employing comprehensiveapproach such as: (a) by integrating of core values into all subjects matter, (b)by implying in all extra-curricular activities, (3) by immersing into Madrasahculture; (3) assessment of character education was conducted via (a) directobservation and (b) evaluation on academic activities (grade report). Thefinding of the research suggest that the role of education management in thecontext of character education program in Madrasah is very important tohandle the program more effective and efficient in order that charactereducation can come up and align with the target and objective of thegovernment’s objective. Therefore, it is in need of Madrasah principals andschool boards’ creativity and innovation to develop and implement charactereducation program professionally, instead of doing the program is just becauseof routine activity. The effective use of school facilities and empowering workethos, school culture and family will significantly support the program ofcharacter education at these mentioned schools.